The Influence of Employee Happiness, Leadership, and Agile Mindset on Work Performance - Kurnia Turrahmi; Dedi Purwana; Agus Wibowo (IJHCM (International Journal of Human Capital Management), 2024)
This study examines the influence of employee happiness, leadership, and agile mindset on work performance. The aim is to provide a comprehensive understanding of how individual and organizational factors interact to enhance employee performance. Data were collected from 200 employees of PT Adhi Karya (Persero) Tbk through a structured survey. The analysis was conducted using structural equation modeling (SEM). The findings reveal that employee happiness has a positive effect on work performance. Leadership that fosters trust and collaboration also has a significant impact on performance. Furthermore, the implementation of an agile mindset in HR practices plays an important role in increasing employee engagement and adaptability, which ultimately improves performance. These results highlight the importance of psychological and organizational factors in enhancing employee outcomes. This study contributes to the organizational behavior literature and offers practical implications for state-owned construction companies in developing leadership strategies, employee well-being, and an agile mindset to optimize performance.